Alkoksidna sol-gel sinteza in luminiscenčne lastnosti SiOspodaj2:Eu - Županc Mežnar, Lea (Kovine zlitine tehnologije, 1999)
Silica doped with europium (?$SiO_2$?:Eu) was prepared by alkoxide sol-gel method using tetraethoxysilane (TEOS) and europium(III) chloride precursors. ?$SiO_2$? monoliths and powders doped with 1-5 mol % Eu were synthesized and compared with undoped ones. The transmission of transparent monolites was measured in UV-visible region. The heating process, which is the final stage in the preparation of powder, was strudied by thermal analyses. The ?$Eu^{3+}$? transitions were determined with fluorescence spectroscopy.
Keywords: luminiscenčne spojine; sol-gel postopki; silicijev dioksid; evropij; karakterizacija